Aggression, Moral Disengagement and Empathy. A Longitudinal Study Within the Interpersonal Dynamics of Bullying - Falla, Daniel; Romera, Eva M.; Ortega-Ruiz, Rosario (Frontiers in Psychology, 2021)
Moral disengagement and empathy have been linked to aggression in traditional bullying. A number of longitudinal studies have focused on how these variables predict aggressive behaviour within the dynamics of bullying. However, no conclusive results have been produced as to whether aggressive behaviour in bullying can predict lower levels of empathy, and to date, no studies have explored in depth the mediating role of moral disengagement strategies in this relationship, which is the aim of this study. A total of 1810 students (51.0% girls; Mage = 14.50; SD = 1.05) completed a survey in three waves at 6-month intervals. The results showed that aggressive behaviour in bullying at Time 1 was inversely related to affective and cognitive empathy at Time 3. Minimization of responsibility, distortion of consequences and dehumanizing mediated in the aggressive behaviour exhibited by the bullying aggressors and in cognitive empathy, while cognitive restructuring and the distortion of consequences mediated in affective empathy. We discuss the impact on moral and emotional sensitivity of the continued aggression occurring in the interpersonal dynamics of bullying, as well as the relationship between certain strategies of moral disengagement and the different types of empathy. We also comment on the need to design intervention programs to address the lowering of moral criteria and empathy in young people and adolescents involved in traditional bullying.